(untitled) (Bangladesh Journal of Zoology, 2021)
With global expansion of vector borne diseases, dengue has emerged as a big health crisis and social problem in recent years in Bangladesh. Despite its endemicity since 2000, very few studies were conducted outside of the Capital Dhaka city regarding vector breeding status. Within this dark situation, the year 2019 reported the ever highest number of dengue cases of 101,354. Of them about 50% were from out of Dhaka. To reduce this burden, keeping the vector population density under threshold level is must. In the present entomological study, 100 houses were checked randomly from five areas of Gazipur City Corporation (GCC) during the month of September in 2019. Both of the Aedes vectors were found in all areas, but Aedes aegypti population was dominant. Rooftop garden and under construction site were identified as the most important vector breeding sites. Highly urbanized area (SA2) produced the highest and suburban area (SA4) produced the lowest Breteau Index (BI) of 110 and 15 respectively. The overall House Index (HI) and Breteau Index (BI) of the study areas were 16 and 49 respectively. Four kinds of containers, namely; cemented tank, drum, big earthen pot (chari) and buckets contained about 80 percent of immature Aedes and identified as key container among the positive containers. The Said study has identified comparatively higher number of Ae. aegypti breeding, which is potential for triggering any major outbreak. Further, large-scale surveillance in all administrative wards with a larger sample may indicate the real picture of vector infestation situation throughout the municipality. Bangladesh J. Zool. 49(1): 69-82, 2021